Does Accessibility to Higher Education matter? Choice Behavior of High School Graduates in the Netherlands - Carla Sá; Raymond J.G.M. Florax; Piet Rietveld (Tinbergen Institute, 2004)
This paper identifies pivotal factors behind individual decision-making in the transition from high school to post-secondary education in the Netherlands. We apply a multinomial logit framework to individual data on post-secondary education choices. Specifically, our modeling approach accommodates two types of effects that have not received ample attention in the literature. First, we include information regarding the geographical accessibility of the higher education system. Second, we allow the individual observations to be correlated within schools in order to account for localized social interactions. Our results confirm the paramount influence of the student's track record and talent. The results, however, also show that geographical proximity to universities or professional colleges significantly increases the probability of high school leavers continuing their education at the post-secondary level.
Keywords: C25; I21; R10; 330; high school graduates; higher education; social interaction; geographical accessibility; Bildungschancen; Studium; Akademiker; Niederlande